2018
DOI: 10.1177/1464993418805171
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional access to financial services: Insights from Indonesia

Abstract: Although better access to financial services is known to lead to various economic opportunities, most studies have approached ‘access’ as a one-dimensional variable, such as availability of services or distance to services. This study proposes approaching access as a multidimensional concept and examining its impact on household economic outcomes. Using panel survey data collected in Indonesia between 2000 and 2014, this study examines how economic, geographical and social aspects of access relate to poverty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Moving focus from micro finance banking, Haini (2021) conceptualized financial inclusion in terms of having access to finance among 51 countries ranked as low and middle-income. On the other hand, Lee and Widyaningrum (2019) focused their study on households in Indonesia and conceptualized financial inclusion in terms of having access to credit by the households. Moving from households, Bokpin et al (2018) focused on Sub-Saharan Africa, sampling manufacturing firms, and conceptualized financial inclusion in terms of having access to finance by the manufacturing firms.…”
Section: Measures Of Financial Inclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving focus from micro finance banking, Haini (2021) conceptualized financial inclusion in terms of having access to finance among 51 countries ranked as low and middle-income. On the other hand, Lee and Widyaningrum (2019) focused their study on households in Indonesia and conceptualized financial inclusion in terms of having access to credit by the households. Moving from households, Bokpin et al (2018) focused on Sub-Saharan Africa, sampling manufacturing firms, and conceptualized financial inclusion in terms of having access to finance by the manufacturing firms.…”
Section: Measures Of Financial Inclusionmentioning
confidence: 99%
“…The study discovered that having access to finance significantly improved the productivity of manufacturing firms as it helped them pursue more profitable projects which previous financial constraints prevented them from pursuing in the past. Lee and Widyaningrum (2019) studied financial access and how it affected the economic empowerment of households in Indonesia and conceptualized economic empowerment in terms of business ownership status and found that access to financial services had a positive pertinent effect on the business ownership status and development.…”
Section: Financial Inclusion and Economic Empowermentmentioning
confidence: 99%
“…Moving focus from micro finance banking, Haini (2021) conceptualized financial inclusion in terms of having access to finance among 51 countries ranked as low and middle-income. On the other hand, Lee and Widyaningrum (2019) focused their study on households in Indonesia and conceptualized financial inclusion in terms of having access to credit by the households. Moving from households, Bokpin et al (2018) focused on Sub-Saharan Africa, sampling manufacturing firms, and conceptualized financial inclusion in terms of having access to finance by the manufacturing firms.…”
Section: Measures Of Financial Inclusionmentioning
confidence: 99%
“…The study discovered that having access to finance significantly improved the productivity of manufacturing firms as it helped them pursue more profitable projects which previous financial constraints prevented them from pursuing in the past. Lee and Widyaningrum (2019) studied financial access and how it affected the economic empowerment of households in Indonesia and conceptualized economic empowerment in terms of business ownership status and found that access to financial services had a positive pertinent effect on the business ownership status and development.…”
Section: Financial Inclusion and Economic Empowermentmentioning
confidence: 99%